Sigmoid Sinus Thrombosis Followed by Splenic Infarction Due to Imatinib Therapy in a Patient with Gastrointestinal Stromal Tumor; Hematological Side Effects of Imatinib - YILMAZ, Hatice; Demirağ, Güzin; Yılmaz, Ali (Journal of Pharmacy & Pharmaceutical Sciences, 2021)
Imatinib has an important place as an adjuvant therapy as well as in the treatment of metastatic disease caused by gastrointestinal stromal tumor (GIST), which is one of the common mesenchymal tumors of the gastrointestinal tract. Imatinib is a tyrosine kinase inhibitor and is generally well tolerated. However, it can cause some serious adverse effects. The most common of these are edema on the face and legs, headache, fatigue, nausea, vomiting, and rash on the skin. The most serious side effects, albeit less common, are gastrointestinal or intraabdominal bleeding. However, thrombotic events such as sigmoid sinus thrombosis and splenic infarction are extremely rare. The current report presents a patient with GIST who is treated with imatinib 400 mg/day. The patient presented with edema on the face and headache in the second month of imatinib therapy, after which she was diagnosed with sigmoid sinus thrombosis. The patient who presented with abdominal pain approximately three months later developed splenic infarction. She was administered acetylsalicylic acid, supplemental oxygen (O2) in the first episode of thrombosis, and imatinib therapy was discontinued. The patient's complaints and thrombus regressed, after which imatinib therapy was resumed. She was administered intravenous hydration, supplemental oxygen, analgesics, and imatinib therapy was discontinued after the patient sustained splenic infarction. After resolution of sigmoid sinus thrombosis and the regression of splenic infarction area, the patient was switched to sunitinib therapy. She is attending routine control visits. Sigmoid sinus thrombosis and splenic infarction should be kept in mind as a rare cause of headache and abdominal pain in patients treated with imatinib, and detailed neurological and gastrointestinal evaluation should be performed.